Tooth acellular extrinsic fibre cementum incremental lines in humans are formed by parallel branched Sharpey’s fibres and not by its mineral phase - Couoh, Lourdes R.; Bucio, Lauro; Ruvalcaba, José Luis; Manoel, Britta; Tang, Tengteng; Gourrier, Aurélien; Grandfield, Kathryn (Journal of structural biology, 2024)
[Display omitted] In humans, the growth pattern of the acellular extrinsic fibre cementum (AEFC) has been useful to estimate the age-at-death. However, the structural organization behind such a pattern remains poorly understood. In this study tooth cementum from seven individuals from a Mexican modern skeletal series were analyzed with the aim of unveiling the AEFC collagenous and mineral structure using multimodal imaging approaches. The organization of collagen fibres was first determined using: light microscopy, transmission electron microscopy (TEM), electron tomography, and plasma FIB scanning electron microscopy (PFIB-SEM) tomography. The mineral properties were then investigated using: synchrotron small-angle X-ray scattering (SAXS) for T-parameter (correlation length between mineral particles); synchrotron X-ray diffraction (XRD) for L-parameter (mineral crystalline domain size estimation), alignment parameter (crystals preferred orientation) and lattice parameters a and c; as well as synchrotron X-ray fluorescence for spatial distribution of calcium, phosphorus and zinc. Results show that Sharpey’s fibres branched out fibres that cover and uncover other collagen bundles forming aligned arched structures that are joined by these same fibres but in a parallel fashion. The parallel fibres are not set as a continuum on the same plane and when they are superimposed project the AEFC incremental lines due to the collagen birefringence. The orientation of the apatite crystallites is subject to the arrangement of the collagen fibres, and the obtained parameter values along with the elemental distribution maps, revealed this mineral tissue as relatively homogeneous. Therefore, no intrinsic characteristics of the mineral phase could be associated with the alternating AEFC incremental pattern.